Impact Angle Constraint Guidance Against Active Defense Target Based on Partial Differential Games - Biao Xu; Jialuo Xu; Shuang Li; Jinpeng Zhang (International Journal of Aerospace Engineering)
For intercepting active defense target, an impact angle constraint guidance law is proposed based on partial differential games. First, the relative motion models of three-player games between interceptor, target, and defense missile are established. The problem of intercepting active defense target is separated into two partial games. Then, two partial coupled game guidance laws are obtained, respectively. Impact angle constraint is taken into account in the game between attacker and defender (D). Finally, a combined guidance law is calculated by the two partial differential games. The performance of the strategy can be adjusted by the weight coefficient related to the miss distance between the attacker and the D. Simulations show that the guidance law can intercept the target with impact angle constraint and evade D’s interception at the same time.